Peter Van Schaack papers - Van Schaack, Peter, 1747-1832.; Van Schaack, Henry, 1733-1823.
Chiefly letters received by Peter Van Schaack after his return to New York together with a few letters of Henry Van Schaack. Correspondents include Loring Andrews, Cadwallader Colden, Abraham Cuyler, James Duane, Edmund Fanning, Jacob Ford, Ezekiel Gilbert, Henry Glen, Richard Harrison, John Sloss Hobart, John Honeywood, Moses Kent, Peter Robert Livingston, George D. Ludlow, Hosea Moffitt, Roger Morris, Thomas Morris, William Powers, Caleb S. Riggs, Theodore Sedgwick, Philip Skene, Robert Troup, John E. Van Alen, John Van Rensselaer, John Watts, Oliver Wendell, and John C. Wynkoop.
In part, handwritten transcripts.
Lawyer, of Kinderhook, N.Y., whose Loyalist sympathies removed him to England from 1778 to 1785. After his return to New York, Peter Van Schaack trained lawyers and was active in New York and national politics. Also represented is his brother, Henry Van Schaack, who served in the French and Indian War, was engaged in New York politics during the Revolution, later farmed in Pittsfield, Mass., which he represented in the state legislature, and retired to Kinderhook, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Andrews, Loring, -- 1768-1805 -- Correspondence; Colden, Cadwallader, -- 1722-1797 -- Correspondence; Cuyler, Abraham, -- 1742-1810 -- Correspondence; Duane, James, -- 1733-1797 -- Correspondence; Fanning, Edmund, -- 1739-1818 -- Correspondence; Ford, Jacob -- Correspondence; Gilbert, Ezekiel, -- 1756-1841 -- Correspondence; Glen, Henry, -- 1739-1814 -- Correspondence; Harrison, Richard, -- 1750-1841 -- Correspondence; Hobart, John Sloss, -- 1738-1805 -- Correspondence; Honeywood, John -- Correspondence; Kent, Moses -- Correspondence; Livingston, Peter Robert, -- 1766-1847 -- Correspondence; Ludlow, George D. -- 1734-1808 -- Correspondence; Moffitt, Hosea, -- 1757-1825 -- Correspondence; Morris, Roger, -- 1727-1794 -- Correspondence; Morris, Thomas, -- 1771-1849 -- Correspondence; Powers, William, -- active 1792 -- Correspondence; Riggs, Caleb S. -- 1756-1825 -- Correspondence; Sedgwick, Theodore, -- 1746-1813 -- Correspondence; Skene, Philip, -- approximately 1720-1810 -- Correspondence; Troup, Robert, -- 1757-1832 -- Correspondence; Van Alen, John E. -- 1749-1807 -- Correspondence; Van Rensselaer, John -- Correspondence; Watts, John, -- 1715-1789 -- Correspondence; Wendell, Oliver, -- 1733-1818 -- Correspondence; Wynkoop, John C. -- Correspondence; American loyalists -- New York (State); Law -- Study and teaching -- New York (State); Kinderhook (N.Y.) -- History; Massachusetts -- Politics and government -- 1775-1865.; New York (State) -- History -- Revolution, 1775-1783.; New York (State) -- Politics and government -- 1775-1865.; Pittsfield (Mass.) -- History; United States -- History -- French and Indian War, 1754-1763.; United States -- History -- Revolution, 1775-1783.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1865.; Lawyers